1999
DOI: 10.1038/sj.jhh.1000783
|View full text |Cite
|
Sign up to set email alerts
|

A new treatment of severe pre-eclampsia by long-term epidural anaesthesia

Abstract: We hypothesised that long term epidural anaesthesia suppresses sympathetic overactivity in pre-eclampsia. Two equal groups of severe pre-eclamptic patients were treated either with long-term epidural anaesthesia (epidural group) or bed rest, diet control, and an antihypertensive drug (control group). After 7 days of epidural block, mean arterial blood pressures decreased, platelet count and serum total protein increased in all cases while proteinuria decreased in four cases. All patients treated with a long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The sympathetic blockade provoked by epidural analgesia causes vasodilation in the lower half of the body that may increase placental perfusion in women with preeclampsia, if perfusion pressure is maintained. There have been several studies in which the effect of epidural analgesia was analyzed in patients with preeclampsia and IUGR and are in agreement with the results obtained in our study [40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 92%
“…The sympathetic blockade provoked by epidural analgesia causes vasodilation in the lower half of the body that may increase placental perfusion in women with preeclampsia, if perfusion pressure is maintained. There have been several studies in which the effect of epidural analgesia was analyzed in patients with preeclampsia and IUGR and are in agreement with the results obtained in our study [40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 92%
“…Kanayama et al [5] reported benefi cial effects of epidural local anesthetic administration on clinical parameters and fetal outcome in patients with pre-eclampsia. We took a different approach; instead of including mothers with a specifi c disease state, we studied fetuses with growth retardation independent of cause.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kanayama et al [5] reported that lumbar epidural local anesthetic (bupivacaine 0.25%, 2 ml/h for 15-26 days) improved blood pressures, platelet count and serum protein levels, and increased duration of pregnancy and birth weight of infants in severely pre-eclamptic women, as compared with a control group receiving standard therapy. These benefi cial effects may be related to the ability of epidural local anesthetics to improve placental blood fl ow.…”
mentioning
confidence: 99%
“…On the contrary, previous studies have reported that mild to moderate intensity exercise did not increase muscle sympathetic nerve activity in non‐pregnant subjects . The growing uterus in the TM3 subjects presses the abdominal sympathetic ganglion and restricts the movement of the thorax, which might explain the increased sympathetic activity during mild intensity exercise …”
Section: Discussionmentioning
confidence: 71%